Extracorporeal Shock Waves Therapy Delivered by Aries Improves Erectile Dysfunction in Spontaneously Hypertensive Rats Through Penile Tissue Remodeling and Neovascularization. Issue 4 (21st September 2019) - Assaly, Rana; Giuliano, François; Clement, Pierre; Laurin, Miguel; Favier, Maryline; Teo, Pearline; Bernabe, Jacques; Alexandre, Laurent; Behr-Roussel, Delphine
Abstract: Background: Low-intensity extracorporeal shock wave therapy (Li-ESWT) has been reported to improve erectile function in patients with moderate-to-severe erectile dysfunction (ED) or even convert phosphodiesterase type 5 inhibitors nonresponders to responders. ED is highly prevalent in hypertensive patients. The effect of Li-ESWT on an animal model of hypertension-associated ED has not been reported. Aim: To investigate the effect of Li-ESWT on hypertension-associated ED and provide plausible mechanisms of action of Li-ESWT on local mechanisms of penile erection. Methods: Spontaneously hypertensive rats (SHRs) in the active group (n = 13) received Li-ESWT at energy flux density 0.06 mJ/mm 2 (Aries; Dornier MedTech, Wessling, Germany) twice weekly for 6 weeks. The emitter was set to zero for SHRs in the sham group (n = 12). Erectile function was assessed 4 weeks post-treatment by monitoring intracavernosal pressure (ICP) in response to electrical stimulation of cavernous nerve before and after single dose of 0.3 mg/kg intravenous sildenafil. Cavernosal tissue was then evaluated for collagen/smooth muscle content, neuronal nitric oxide synthase (nNOS), and vascular endothelial factor (CD31) expression. Outcomes: Erectile function was assessed with ICP, erectile tissue remodeling was studied by smooth muscle/collagen ratio, nNOS and CD31 were semiquantitatively evaluated on cavernosal sections. Results: The improvement of ICP parameters was greater in Li-ESWT–treated rats compared with controls with and without sildenafil. Sildenafil led to 20% increase in area under the intracavernosal pressure curve measured during the entire response/mean arterial pressure at 10 Hz in ESWT_SHR + sildenafil compared with ESWT_SHR. The smooth muscle/collagen ratio increased 2.5-fold in Li-ESWT compared with sham. Expression of CD31 tended to be increased whereas nNOS was unchanged. Conclusions: Li-ESWT by Aries may represent an effective noninvasive therapeutic alternative and a relevant add-on therapy to phosphodiesterase type 5 inhibitors for ED in hypertensive patients, and it is suggested that it acts via remodeling of the penile tissue and promoting cavernosal vascularization.